Transcranial Supraorbital Approach for Tumor Removal of Spheno-Orbital Meningioma with Favorable Clinical Outcomes - Nina Asrini Noor; Neni Anggraini; Mutmainah Mutmainah; Renindra Ananda Aman (Majalah Oftalmologi Indonesia, 2016)
Background: To describe and evaluate the surgery results regarding resectability and clinical outcomes oftranscranial supraorbital approach for tumor removal of spheno-orbital meningiomaCase Illustration: A 58-year-old woman presented with proptosis of the right eye since 9 years prior.At initial examination, visual acuity was 6/15 with significant nasal visual field defect. There wereprominent proptosis and inferior globe displacement of the right eye with no palpable mass. A frontoparietalbone deformity was also observed. CT scan examination revealed hyperostosis of sphenoid,frontal, and temporal bone with extensive intraorbital mass with contrast enhancement suggestive ofmeningioma. Incisional biopsy was the performed and confirmed the histopathological diagnosis ofmeningothelial meningioma (WHO grade 1). Transcranial supraorbital in conjunction with lateralorbitotomy was performed in this patient as the definitive treatment for tumor removal of sphenoorbitalmeningioma. Craniotomy and opening of orbital roof were carried out by neurosurgeon toexpose intraorbital region. Total tumor removal was than completed.Conclusion: Transcranial supraorbital approach is an effective surgery for spheno-orbital meningiomaremoval as it offers excellent exposure. A radical resection through transcranial approach can be achievedwith low morbidity, providing a significantly improved clinical outcome in long term period. In thiscase, the spheno-orbital meningioma was grossly resected totally with excellent visual outcome andacceptable cosmetic appearance.Keywords: spheno-orbital meningioma, transcranial approach, tumor resection